PENGARUH BRAND POSITIONING DAN CONSUMPTION VALUE TERHADAP CONSUMER CHOICE BEHAVIOR (STUDI PADA PENGGUNA LAYANAN DATA XL) - Kurniawan, Oki (Journal of Innovation in Business and Economics, 2016)
Expansion of cellular network that provide faster data access makes rivalry between cellular operator switch from voice and sms to data service. This study has an objective to explore the influence of brand position to consumer choice behavior with consumption values as moderating variable based on Theory of Consumption Values in the context of XL data service. Brand positioning as a marketing stimuli has an important role as value creation that create a value to fill the consumer wants and needs. Hypothesis testing was performed with Structural Equation Model-Partial Least Square (SEM-PLS) on data collected from 163 mobile data users. This study proves that consumption values as mediator to connect the relationship between brand positioning and consumer choice behavior.Keywords: Brand Positioning, Consumption Values, Consumer Choice Behavior, Telecommunication, SEM-PLS